Powertrain test cell and its test procedure development for greenhouse gas emission measurements. (2015) - Anthony, Joseph W.; Sarlashkar, Jayant V.; Phan, Anthony; Roberts, Charles E.; Zhang, Houshun; Sanchez, James; Spears, Matthew; Cullen, Angela
The Environmental Protection Agency (EPA) and the Department of Transportation's National Highway Traffic Safety Administration (NHTSA) announced a first-ever program to reduce greenhouse gas (GHG) emissions and improve fuel efficiency of heavy-duty trucks and buses in 2011. The rule was the first phase of the multi-phase GHG reduction approach. The agencies, working together with industry stakeholders, are currently developing different concepts that could be considered for determining compliance with any future phase of GHG and fuel efficiency regulations. The agencies are evaluating a wide array of options, including full vehicle simulation, engine-in-the-loop (EIL) testing, powertrain-in-the-loop (powertrain) testing, and chassis dynamometer testing. Each method has advantages and disadvantages. Full vehicle simulation is ideal for repeatability and managing a large number of vehicle configurations, but it is generally accepted that high-accuracy simulation of the thermal, chemical, and fluid dynamic processes in the engine and aftertreatment is very difficult to achieve. EPA and SwRI have developed a powertrain test cell for the purposes of evaluating powertrain test correlation with chassis testing and simulation results, and validating simulation models. This paper describes the sizing of a powertrain test cell, modifications required to a standard engine test cell for powertrain testing, and a comparison to chassis dynamometer results.